VITILIGO - An Overview - Jakku, Rasagna; Thappatla, Vasundhara; Kola, Tejaswini; Kadarla, Rohith Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Vitiligo is a common, disfiguring autoimmune disease that negatively affects patients’ self-esteem and quality of life. Vitiligo is a common acquired disorder of skin depigmentation in varying patterns, varying from small macules with scalloping borders to near-total depigmentation of body. The presence of autoimmune diseases like autoimmune thyroiditis, Grave’s disease, Addison’s disease, diabetes mellitus, alopecia areata, and pernicious anemia in patients and their first degree relatives favours its autoimmune etiology. Clinically, the usual age of onset is before 20 years of age in nearly half of the cases. It affects both genders equally at any age but most studies report a peak incidence between 18 and 21 years (mean 24 years).